SOCIAL JUSTICE IMPLICATIONS OF INCLUSIVE MEASURES OF SEXUAL AND GENDER MINORITY POPULATIONS - Bragg, Jedediah (My University, 2017)
The understanding of human sexuality has continued to expand, and has led to an increased understanding of the diversity comprising the sexual and gender minority population. Despite this broadened knowledge base, researchers continually assess sexuality by less-than inclusive means. As such, there are extensive variations in population estimates. The primary focus of this study is to explore the impact of expanding the assessment of SGM status. The secondary focus of this study is to explore how positive social institutions affect well-being through hope. Study participants (N = 628) completed an anonymous online questionnaire answering two series of items about sexuality as well as items assessing positive social institutions, hope, and flourishing. Results indicate a significant change (p < .001) in proportions of those identifying as sexual and gender minority based on two different assessment methods. Further, SEM results support that social supports drive hope (B = .772, p < .001; BCa 95% CI [.717, .820]) which, in turn, drives flourishing (B = .476, p < .001; BCa 95% CI [.348, .587]). Finally, the sexual and gender minority population report lower rates of social supports, hope, and flourishing compared to the cisgender/heterosexual population (p < .001). These findings suggest the importance of inclusively assessing sexuality and the role that social supports serve in building hope and flourishing, and that interventions need to be designed to address the lower levels of social supports in the sexual and gender minority population in order to impact levels of hope and flourishing.
Keywords: flourishing, hope, positive psychology, LGBTQ, sexual and gender minority, sexuality, social support